Tingkat Perilaku Konsumtif Mahasiswa Perantau Membeli Produk Online Pada Program Studi Bimbingan dan Konseling USD - Geovani, Kamelia; Arswimba, Bernardinus Agus (SOLUTION, 2023)
This study aims to: (1) Identify how high the level of consumptive behavior of overseas students of the guidance and counseling study program at Sanata Dharma University Yogyakarta buys online products. (2) Knowing the items on the consumptive behavior scale of overseas students buying online products at Sanata Dharma University which are identified as very high which can be proposed as guidance topics. This type of research is descriptive quantitative research. The subjects of this study were 50 students of the Guidance and Counseling Study Program at Sanata Dharma University, Yogyakarta. Data collection uses a scale of Consumptive Behavior Level with 49 valid items and has a Cronbach Alpha Reliability index of 0.959. The data collection technique used a questionnaire with a modified Likert scale and was compiled based on aspects of consumptive behavior: (1) Impulsive Purchases, (2) Excessive Purchases, (3) Irrational Purchases. Data analysis techniques using descriptive statistics. The results of this research show that: (1) Based on the results of the Consumptive Behavior Level scores of migrant students from the Guidance and Counseling Study Program at Sanata Dharma University Yogyakarta, it was found that 25 (50%) migrant students had very high levels of consumptive behavior, 5 (10%) students migrants who have a moderate level of consumptive behavior, 20 (40%) migrant students who have a very low level of consumptive behavior; (2) The results of the research instrument item categorization found that 10 (20%) item scores were classified as Medium, 15 (31%) item scores were classified as Low, and 24 (49%) item scores were found to be classified as Very Low